Role of regulation of PD-1 and PD-L1 expression in sepsis - Zhang, Teng; Yu-Jing, Li; Ma, Tao (Frontiers in Immunology, 2023)
Long term immunosuppression is problematic during sepsis. The PD-1 and PD-L1 immune checkpoint proteins have potent immunosuppressive functions. Recent studies have revealed several features of PD-1 and PD-L1 and their roles in sepsis. Here, we summarize the overall findings of PD-1 and PD-L1 by first reviewing the biological features of PD-1 and PD-L1 and then discussing the mechanisms that control the expression of PD-1 and PD-L1. We then review the functions of PD-1 and PD-L1 in physiological settings and further discuss PD-1 and PD-L1 in sepsis, including their involvement in several sepsis-related processes and their potential therapeutic relevance in sepsis. In general, PD-1 and PD-L1 have critical roles in sepsis, indicating that their regulation may be a potential therapeutic target for sepsis.